2009
DOI: 10.1108/13595474200900014
|View full text |Cite
|
Sign up to set email alerts
|

Social inclusion: life after ‘day services’

Abstract: Traditionally, participation in the local community has been considered a crucial component of community living for people with learning disabilities. Highlighted in Valuing People (DH, 2001) and in Valuing People Now (DH, 2007), this concept ‐ now appearing as ‘inclusion’ ‐ has retained its prominence, and is an important area for service development and monitoring. Monitoring of community activities was undertaken pre‐ and post‐closure of two small day service facilities. The findings indicate that for this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Special consideration is needed in the change process for those with profound, multiple and complex needs to ensure that suitable facilities, adequately trained staff and specialist resources are available in any new models of care (Leyin and Kauder, 2009). For example, one study from The Netherlands found that 63% of the day centre activities for this group were 'care-related', for instance, waiting and resting, starting and finishing the day.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Special consideration is needed in the change process for those with profound, multiple and complex needs to ensure that suitable facilities, adequately trained staff and specialist resources are available in any new models of care (Leyin and Kauder, 2009). For example, one study from The Netherlands found that 63% of the day centre activities for this group were 'care-related', for instance, waiting and resting, starting and finishing the day.…”
Section: Introductionmentioning
confidence: 99%
“…There was no significant increase in community activities or social inclusion.Even though, for some individuals, some gains were recorded, overall these gains were considered a poor return for the hours released from the closure of the day service facilities. (Leyin and Kauder, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…This may indicate a continued preference for day care on the part of some service users; yet recent closures of many such centres suggest that such a choice might not be available in the future. Leyin and Kauder (2009) warned that for people with learning disabilities (particularly those who are older, with higher support needs) the closure of day service facilities does not, overall, result in a significant increase in participation in community activities.…”
Section: Introductionmentioning
confidence: 99%